Donor adipose-derived stromal cells are vasoprotectant but unable to revert acute rejection in rodent vascularized composite allotransplants - Schweizer, Riccardo; Kamat, Pranitha; Klein, Holger J.; Kollar, Branislav; Waldner, Matthias; Stölzl, Klara; Lehner, Fabienne; Salemi, Souzan; Bode, Peter; Eberli, Daniel; Taddeo, Adriano; Plock, Jan A. (Frontiers in Immunology, 2025)
BackgroundVascularized composite allotransplantation is successful in reconstruction of major defects of the upper extremity and face. Both rejection and vascular damage seriously endanger the outcome. The role of adipose-derived stromal cells (ASCs) in suppressing acute rejection of composite allotransplants and their short-term protective effects on vessels remains widely unexplored.MethodsSystemic and local donor-derived ASCs (CD45−CD29+CD90+) versus FK-506 administration was evaluated for reversal of acute rejection and vascular alterations in fully mismatched rat hind-limb transplants.ResultsASC administration upon grade II rejection significantly delayed but did not suppress progression to grade III rejection (7.6 ± 1.0 days systemic, 7.1 ± 1.1 days local vs. no cell therapy 2.9 ± 1 days; p<0.01, n=38 animals). Pro-inflammatory cytokine blood levels significantly increased in controls from grade II to grade III rejection, whereas ASC significantly lowered the levels for G-CSF, MIP-1α, MIP-3α, IL-1α, IL-1β, IL-18, and Rantes (p<0.05). Local and systemic PKH-26-labeled ASCs homed to the allograft and reversed intragraft vascular alterations in arterioles of rejecting skin and muscle, similarly to FK-506-treated controls (p<0.01).ConclusionsAlthough systemic and local ASC therapy reduces progression of acute rejection in vascularized composite allotransplantation, it is not able to revert rejection without additional immunosuppressive therapy. However, graft vasculitis during acute rejection is significantly reduced after cytotherapy.